Role of San Salvador's Concord in the unity of Central America's Countries 1951 and the Attitude of the United States. (Journal of the College of Basic Education, 2022)
The study aim to acknowledge the nature of San Salvador's Concord in uniting Central America's Countries and the attitude of the United States, many attempts were carried to establish the unity among the five Republics of Central America, uniting especially after gaining indepense , of Spanish Colonization since 1821, were it was exposed to a second invasion, which, the Mexicon and managed ending it in 1822, First attempt to establish unity among these countries dates back to 1824 it lasted to a period of time as aresult of facing foreign threats , afterward numerous attempts Came in 1838, all these attempts hadn’t lasted long due to the ongoing Conflicts among leaders and Competition upon leadership.The attempts Continued untill 1907 when the Court of Justice was established in Central America to on look the disputes when United states and Mexico interferrd Washington Conference was held in 1922, througout this Conference many ConCords were issued, despite these attempts never succeeded untill 1951 when the Five Countries of Central America signed San Salvador agreement, and it became active on 14 Dec 1951 and through it, the Organization of Central America was established, this, was by the aid and assistance of the U.S.A to fulfil its own interests